Optimasi Kondisi Proses Pembuatan Pulp Tandan Kosong Sawit - Rafi, M Khaidiz; Helwani, Zuchra; Rionaldo, Hari; Zulfansyah, Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The use of wood for paper making in Indonesia can be reduced by biomass materials and non-wood raw materials. Indonesia is the country that produces the largest palm oil in the world with a total oil palm plantation area of 11 million Ha and a total palm oil production of 33 million tons / year [Ministry of Agriculture, 2016]. Reduce palm oil mill waste can be use by utilizing oil palm empty fruit bunch as alternative raw material in making paper. A central composite design (CCD) and response surface methodology (RSM) were employed to optimize the soda pulping of oil palm empty fruit bunch. The effects of three independent variables are temperature (120oC, 130oC and 140oC), cooking time (60, 120 and 180 min), solid to liquor ratio (1/8, 1/10 and 1/12) on pulp yield, lignin content, and physical properties of pulp were investigated. The major parameter influencing was the solid to liquor ratio for pulp yield and lignin content. According to the response surface analysis the optimum conditions for yiled pulp 50,66% and lignin content of 5,2% would be obtained using a cooking time of 60 minute, at 180◦C and with a solid to solid to liquor ratio of 1/12 with desirability value 0.788. On the physical characteristics of the pulp the value obtained for the burst index is 21.769 kPa m2/g, tensile index 0.570875 mN.m2/g and tear index 548.791 mN/g.Keywords: oil palm empty fruit bunch, optimization, CCD, RSM.